2005
DOI: 10.1111/j.1492-7535.2005.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning in end‐stage renal disease patients: Update 2005

Abstract: Physical functioning in patients with end-stage renal disease treated with dialysis is low, whether measured using objective laboratory measures, physical performance testing, or self-reported measures. Peak oxygen uptake (VO2peak), self-reported functioning measures, and physical activity levels are independent predictors of mortality in these patients. Cardiovascular exercise training studies result in improvements in VO2peak, physical performance tests, and self-reported functioning. Resistance exercise tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
151
1
23

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(181 citation statements)
references
References 104 publications
(231 reference statements)
6
151
1
23
Order By: Relevance
“…Studies have demonstrated the effectiveness of treatments for several of the conditions, including impaired physical function (6,30), pain (31), and depression (32,33). The co-occurrence of multiple conditions would appear to be a formidable barrier to their successful treatment because of the need for many interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of treatments for several of the conditions, including impaired physical function (6,30), pain (31), and depression (32,33). The co-occurrence of multiple conditions would appear to be a formidable barrier to their successful treatment because of the need for many interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While 98.6% of U.S.A. nephrologists who were present at the Meeting of the American Society of Nephrology in 2001 have recognized the benefits of PA, only 28.5% were prescribing exercises to their patients 30 , which draws attention to the investigation of the reasons why this prescription or referral for the practice of PA is not being properly considered. Studies have shown the benefits of PA on the relief of depressive and psychological well-being symptoms 31,32 , with reduction of the BDI score after a program of intra-dialysis aerobic exercises in patients undergoing HD 33 , as well as the Brazilian Society of Nephrology itself recommends the practice of regular physical activity as a non-pharmacological measure for the control of CKD 34 . It was observed, in this study, that most part of the sedentary consisted of subjects who used to be inactive before the four years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide additional support to the promotion of physical activity programs in hemodialysis units. Despite the evidence supporting a role of physical activity in improving outcomes, the nephrology community has apparently not emphasized counseling and exercise programs to improve physical activity for patients on MHD (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%